2014
DOI: 10.1517/14728222.2014.940893
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mitochondrially mediated plasticity to develop improved therapeutics for bipolar disorder

Abstract: Introduction Bipolar disorder (BPD) is a severe illness with few treatments available. Understanding BPD pathophysiology and identifying potential relevant targets could prove useful for developing new treatments. Remarkably, subtle impairments of mitochondrial function may play an important role in BPD pathophysiology. Areas covered This article focuses on human studies and reviews evidence of mitochondrial dysfunction in BPD as a promising target for the development of new, improved treatments. Mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 159 publications
(187 reference statements)
0
36
0
Order By: Relevance
“…Although accumulating evidence points towards mitochondrial dysfunction in psychiatric disorders (Manji et al, 2012), the therapeutic potential of mitochondrial targeting has only been recently highlighted for bipolar disorder (de Sousa et al, 2014) and autism (Ghanizadeh et al, 2013) and has never been tested in vivo. Our study is the first in vivo application of selective mitochondrial targeting in the context of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Although accumulating evidence points towards mitochondrial dysfunction in psychiatric disorders (Manji et al, 2012), the therapeutic potential of mitochondrial targeting has only been recently highlighted for bipolar disorder (de Sousa et al, 2014) and autism (Ghanizadeh et al, 2013) and has never been tested in vivo. Our study is the first in vivo application of selective mitochondrial targeting in the context of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 might regulate Ca 2þ signals by interacting with the inositol 1,4,5-trisphosphate receptor to provoke cell survival (Distelhorst and Bootman, 2011). In addition, mitochondrial dysfunction could affect apoptosis, Ca 2þ signaling and oxidative stress in bipolar disorder (de Sousa et al, 2014). Therefore, mitochondrial dysfunction might influence Bcl-2 protein levels in bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been implicated in BD [7,8,9,10]. The energy dysregulation has been characterized by increased reactive oxygen species production, decreased mitochondrial complex subunits in the brain, ATP-dependent proteasome degradation, and an increase in lactate with a corresponding decreased intracellular pH [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the role of the mitochondrial genome in BD risk has revealed candidate associations with mitochondrial point mutations, deletions, haplogroups (subjects sharing the same maternal ancestral haplotypes), and copy number variations [19,20,21,22]. For instance, the rare mtDNA mutation 3644T>C was found to be associated with BD [7,19]. In addition, various mitochondrial single-nucleotide polymorphisms (mtSNPs) have been proposed to be associated with BD [19,22,23,24].…”
Section: Introductionmentioning
confidence: 99%